Solitary plasmacytoma extramedullary to duodenal level: an unusual case of intestinal occlusion - Manuel Lorenzo López Reboiro; Inés Navarro Menéndez; Lucía Cid Conde; José López Castro (Sociedade Galega de Medicina Interna, 2019)
Plasma cell neoplasms represent only 1-2% of hematological malignancies and intestinal plasmocytoma represents only 3%. Extramedullary plasmocytomas most commonly are located in upper airway and oral cavity; the gastrointestinal plasmocytoma only represents 12%, the most frequent being the gastric one. We present a brief report about an extramedullary solitary plasmocytoma at the intestinal level (duodenum).